UTILITAS SISTEM ANTRIAN PADA PT. PEGADAIAN (PERSERO) CABANG RAPPANG - Fatimah, Fatimah; Arfianty, Arfianty; Agustina, Nelly (Economos : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the level of utility queuing system at PT. Pegadaian (Persero) Rappang Branch. The data collection techniques used in this study are interviews and observation. The population used in this study were all customers who came to PT. Pegadaian (Persero) Rappang Branch at 08.00-12.00 and 13.00-15.00. The data analysis technique in this study uses a descriptive method, which is a way of analyzing data by comparing the problem with existing theories, besides that, a formula is also used to solve the queue problem in PT. Pegadaian (Persero) Rappang Branch. The results of calculations using the M/M/S queuing method at PT. Pegadaian (Persero) Rappang Branch applies queue discipline, namely First Come First Server (FCFS). From the results of calculations using the queuing system method with multiple lines (M/M/S), it is known that the probability that there are 0 people in the system (no customers in the system) P0 is 8.78%, while the utility level of pawnshops/busyness P is 68% of the time that does not work. used 32% (empty service hours).